Recent Publications (Quarterly Journal of Economics, 1969)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 83, Issue 1, February 1969, Pages 171–172, https://doi.org/10.1093/qje/83.1.171 Published: 01 February 1969